Improving Financial Stability: How Good Corporate Governance Can Prevent Financial Distress - Angraini, Fadila; Rahayu, Sovi Ismawati (Santoso Academy Network, 2025)
This research aims to examine the influence of Good Corporate Governance as proxied by the size of the Board of Directors, Independent Commissioners, Audit Committee and Institutional Ownership on Financial Distress partially or simultaneously. The research method used is quantitative and uses secondary data, namely service firms, one of which is the transportation sector, which is listed on the Indonesia Stock Exchange. The sample used was 7 issuers and the results were obtained using a purposive sampling method. The analytical method used is multiple linear regression analysis techniques. The results of this research show that overall, the size of the Board of Directors, Independent Commissioners, Audit Committee and Institutional Ownership variables partially or simultaneously influence Financial Distress. Managerial Implications for the study on the effect of good corporate governance on financial distress highlight the critical role of robust governance practices in mitigating financial risks and ensuring organizational stability. Implementing strong governance mechanisms such as effective board oversight, transparent financial reporting, and adherence to regulatory requirements can significantly reduce the likelihood of financial distress.